β-Myrcene Mitigates Colon Inflammation by Inhibiting MAP Kinase and NF-κB Signaling Pathways - Almarzooqi, Saeeda; Venkataraman, Balaji; Raj, Vishnu; Alkuwaiti, Sultan Ali Abdulla; Das, Karuna M.; Collin, Peter D.; Adrian, Thomas E.; Subramanya, Sandeep B. (Molecules (Basel, Switzerland), 2022)
Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders that include Crohn’s disease (CD) and ulcerative colitis (UC). The incidence of IBD is rising globally. However, the etiology of IBD is complex and governed by multiple factors. The current clinical treatment for IBD mainly includes steroids, biological agents and need-based surgery, based on the severity of the disease. Current drug therapy is often associated with adverse effects, which limits its use. Therefore, it necessitates the search for new drug candidates. In this pursuit, phytochemicals take the lead in the search for drug candidates to benefit from IBD treatment. β-myrcene is a natural phytochemical compound present in various plant species which possesses potent anti-inflammatory activity. Here we investigated the role of β-myrcene on colon inflammation to explore its molecular targets. We used 2% DSS colitis and TNF-α challenged HT-29 adenocarcinoma cells as in vivo and in vitro models. Our result indicated that the administration of β-myrcene in dextran sodium sulfate (DSS)-treated mice restored colon length, decreased disease activity index (DAI), myeloperoxidase (MPO) enzyme activity and suppressed proinflammatory mediators. β-myrcene administration suppressed mitogen-activated protein kinases (MAPKs) and nuclear factor-κB (NF-κB) pathways to limit inflammation. β-myrcene also suppressed mRNA expression of proinflammatory chemokines in tumor necrosis factor-α (TNF-α) challenged HT-29 adenocarcinoma cells. In conclusion, β-myrcene administration suppresses colon inflammation by inhibiting MAP kinases and NF-κB pathways.